2020
DOI: 10.1002/jso.25822
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of muscle depletion assessed by computed tomography for surgical outcomes of cancer patients undergoing total esophagectomy and gastrectomy

Abstract: Introduction Considering the high morbimortality rate in oncologic surgeries of the gastrointestinal tract, especially in patients with malnutrition, the use of predictive tools is necessary, since preoperative strategies could improve postoperative outcomes. Objectives To evaluate body composition by computed tomography and its association with morbimortality post esophagectomy and total gastrectomy. Methods Prospective cohort study (n = 80). Sociodemographic, diagnostic, treatment and postoperative data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…In this study, we found that the myotomy length was associated with changes in energy metabolism during the perioperative period of POEM. Previous reports have discussed the prognostic and risk factors for complications of ESD and other surgical procedures [ 59 , 60 , 61 ]. Age [ 62 , 63 ], body mass index (BMI) [ 64 , 65 ], surgical duration [ 66 ], resection area [ 32 ], and nutritional status [ 67 , 68 ] are commonly reported factors.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the myotomy length was associated with changes in energy metabolism during the perioperative period of POEM. Previous reports have discussed the prognostic and risk factors for complications of ESD and other surgical procedures [ 59 , 60 , 61 ]. Age [ 62 , 63 ], body mass index (BMI) [ 64 , 65 ], surgical duration [ 66 ], resection area [ 32 ], and nutritional status [ 67 , 68 ] are commonly reported factors.…”
Section: Discussionmentioning
confidence: 99%
“…New prognostic markers for patients with pancreatic cancer are still under investigation. Recently, some studies suggested that malnutrition, sarcopenia, and inflammation might have an effect on survival in patients with malignancies (11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia is defined as a reduction in muscle mass and muscle strength. In some studies it was seen that cancer patients with sarcopenia had worse prognoses (14)(15)(16)(17). We aimed to investigate the possible association between psoas muscle mass, inflammation, nutritional status at the time of diagnosis, and survival in patients with pancreatic adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…La evolución de los métodos de imagen combinada con la rápida evolución del aumento de la capacidad de procesamiento rápido de datos de imágenes, principalmente a través de herramientas de inteligencia artificial, con la facilitación de la segmentación automática de estructuras y órganos, y la realización de cálculos avanzados (incluidas las mediciones de área y volumen) (69), han impulsado el interés por obtener datos de exámenes realizados para cualquier indicación clínica. Esta llamada estrategia oportunista ha sido propuesta para estudios de evaluación de riesgo y pronóstico de diversas condiciones patológicas, incluida la posibilidad de detección del síndrome metabólico(70), predicción de fractura osteoporótica (71), cribado cardiometabólico multiparamétrico (72), predicción de riesgo de adenoma colorrectal (73) y, también, pronóstico para el tratamiento del cáncer (74).…”
Section: Placas No Calcificadas Con Spott Calificationunclassified